Solve for c.
ab - c = 9

Question|Asked by alston2013

Asked 5/4/2015 9:14:32 AM

Updated 5/4/2015 12:44:56 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by Andrew. [5/4/2015 12:44:53 PM]

s

Expert answered|jerry06|Points 31112|

Expert answered|jerry06|Points 31113|

Question|Asked by alston2013

Asked 5/4/2015 9:14:32 AM

Updated 5/4/2015 12:44:56 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by Andrew. [5/4/2015 12:44:53 PM]

Rating

3

The equation of the line, in standard form, that passes through (4, -3) and is parallel to the line whose equation is 4x + y - 2 = 0 is 4x + y = 13

Added 5/4/2015 11:17:54 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [5/4/2015 12:45:19 PM]

Solve for c.
ab - c = 9
**Weegy:** Q - 7 5/6 = 6 1/2 Q = 6 1/2 + 7 5/6 = ((13 X 6) + (47 X 2)) / (2 X 6) = (78 + 94) / 12 = 172/12 = 43/3 = 14 1/3 **User:**
Use the listing method to write the following set.
{x | x N, x **Weegy:** I assume you mean divided by and the answer would be 1 **User:** The length of a rectangle is 3 inches more than its width, and its perimeter is 22 inches. Find the width of the rectangle. **Weegy:** Let x be its width, then its length is (x + 3). perimeter = 2x + 2(x + 3) = 22, solve the equation we get x = 4. Its width is 4 inches. **User:** Given the line 2x - 3y - 5 = 0, find the slope of a line that is perpendicular to this line. **Weegy:** Given the line 2x - 3y - 5 = 0, the slope of a line that is perpendicular to this line is -3/2. **User:** A man invests a certain amount of money at 2% interest and $800 more than that amount in another account at 4% interest. At the end of one year, he earned $92 in interest. How much money was invested in each account? **Weegy:** Let the man invest an amount x at 2% interest.
Then, [ he invests an amount (x+800) at 4% interest.
Total simple interest for one year is
x*2/100 + (x+800)*4/100 = 92
2x+4x+3200 = 9200
6x = 9200-3200
6x = 6000
x = 1000
So the man invested $ 1000 at 2% interest and $ 1800 at 4% interest. ] **User:** What is the algebraic expression for "the difference between seven times a number and three times that number"? **User:** Describe the location of the point that has the following coordinates.
positive abscissa, positive ordinate
**Weegy:** First Quadrant. (More)

Question|Asked by alston2013

Updated 4/30/2015 6:59:20 PM

1 Answer/Comment

ab - c = 9

- c = 9 - ab

c = -9 + ab

- c = 9 - ab

c = -9 + ab

Added 4/30/2015 6:59:20 PM

This answer has been confirmed as correct and helpful.

Simplify 18 - 2[x + (x - 5)].
8 - 4x
28 - 4x
28 - 2x **Weegy:** 18 - 2[x + (x - 5)]
=(-2x + -2x) + (18 + 10)
= -4x + 28 (More)

Question|Asked by alston2013

Expert Answered

Updated 4/30/2015 12:56:14 PM

0 Answers/Comments

A speech given at a graduation ceremony attended by the city mayor should be _____ in style.
semi-formal
formal
informal **Weegy:** A speech given at a graduation ceremony attended by the city mayor should be formal in style. (More)

Question|Asked by alston2013

Updated 11/8/2015 1:46:00 AM

0 Answers/Comments

Solve for x.
3(2x - 3) + 4(2 - x) = 0
**Weegy:** 3(2x - 3) + 4(2 - x) = 0 6x - 9 + 8 - 4x = 0 2x - 1 = 0 2x = 1 x = 1/2 **User:** Given: y varies directly with x and has a constant rate of change of 7.
When the value of y is 12, then the value of x would be _____.
(More)

Question|Asked by alston2013

Not Answered

Updated 5/4/2015 10:14:47 AM

1 Answer/Comment

Given: y varies directly with x and has a constant rate of change of 7. When the value of y is 12, then the value of x would be 12/7 .

If y = 7x

when y = 12

x = 12/7

If y = 7x

when y = 12

x = 12/7

Added 5/3/2015 1:34:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [5/4/2015 10:15:15 AM]

Find the product.
2y^2(3x + 5z) **Weegy:** 2y^2(3x + 5z) = 2y^2*3x + 2y^2*5z = 6xy^2 + 10zy^2 **User:** Find the product.
-2xa(-4xb - 2x^3 + 5x) **Weegy:** -2x^a(-4x^b - 2x^3 + 5x) = -2x^a*(-4x^b) + (-2x^a)*(-2x^3) - 2x^a*5x = 8x^(a+b) + 4x^(3+a) - 10x^(a+1) **User:** Simplify 8y(y - 4) + 3y(y + 2). **Weegy:** 8y(y - 4) + 3y(y + 2) = 8y^2 - 32y + 3y^2 + 6y; = 11y^2 - 26y **User:** Simplify 7(n - p) + 5p. **Weegy:** 7(n - p) + 5p = 7n - 7p + 5p = 7n - 2p **User:** Simplify p(p - q) - q(q - p). **Weegy:** p(p - q) - q(q - p) = p^2 - pq - q^2 + pq = p^2 - q^2 **User:** Simplify 8 + 3{x - 2[x + 5(x + 3)]}. **Weegy:** 8 + 3{x - 2[x + 5(x + 3)]} = 8 + 3{x - 2[x + 5x + 15]} = 8 + 3{x - 2[6x + 15]} = 8 + 3{x - 12x - 30} = 8 + 3{ - 11x - 30} = 8 - 33x - 90 = -33x - 82 (More)

Question|Asked by alston2013

Updated 5/5/2015 11:39:15 AM

0 Answers/Comments

31,881,854

questions answered

There are no comments.